2021
DOI: 10.32718/ujvas4-3.05
|View full text |Cite
|
Sign up to set email alerts
|

Natural biologically active additive in feeding calves

Abstract: Studies on the effectiveness of the inclusion of sodium humate in the diet of young cattle were conducted on four groups of animals. Installed improvement in the consumption of hay by the bulls of the experimental groups by 12.5–20 % compared with the control young was found, as a result of which they consumed more feed units by 1.5, 2.3, and 3.5 %, exchange energy – by 2.4, 3.9 and 5.1 %, digestible protein – by 1.2, 2.1 and 3.7 %. As a result of the inclusion of sodium humate in the diet as part of the KR-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
0
5
0
5
Order By: Relevance
“…Haematological and biochemical tests on the blood of farm animals are necessary to obtain information about their ongoing processes and general physiological state of health. Some research studies have found that humic substances derived from sapropel stimulate haematopoiesis and improve metabolism and immunity [55]; sodium humate possesses antidiarrheal, antimicrobial, anti-inflammatory, and growth-promoting properties, as well [79]. Overall, the blood test parameters of the breeding heifers tested were within the reference intervals [80,81].…”
Section: -3-general Health Status Of the Breeding Heifersmentioning
confidence: 83%
See 4 more Smart Citations
“…Haematological and biochemical tests on the blood of farm animals are necessary to obtain information about their ongoing processes and general physiological state of health. Some research studies have found that humic substances derived from sapropel stimulate haematopoiesis and improve metabolism and immunity [55]; sodium humate possesses antidiarrheal, antimicrobial, anti-inflammatory, and growth-promoting properties, as well [79]. Overall, the blood test parameters of the breeding heifers tested were within the reference intervals [80,81].…”
Section: -3-general Health Status Of the Breeding Heifersmentioning
confidence: 83%
“…During this period, the heifers were fed a small amount of NaHum at an intake rate of 0.3 mL of NaHum per kg of live weight. At the beginning of the experiment-at stage 1 of each replication-the heifers were fed 0.4 mL of NaHum per kg of live weight, gradually increasing it to 0.6 mL at stage 3 (Table 2), which was in line with the methodology for dietary experiments conducted by scientists from other countries [55]. During the experiment, the rate of intake of NaHum was adjusted every 5 days according to the daily live weight gain of the heifers in the previous period and the expected live weight.…”
Section: -3-principles Of Establishing Groups Of Breeding Heifers a D...mentioning
confidence: 93%
See 3 more Smart Citations